Community mental health teams for older people: variations in case mix and service receipt (II). (9th September 2014) - Wilberforce, Mark; Tucker, Sue; Brand, Christian; Abendstern, Michele; Jasper, Rowan; Stewart, Karen; Challis, David
<x xml:space="preserve">Abstract</x> Objectives To determine the extent to which services provided to older people via community mental health teams (CMHTs) vary in duration, composition and intensity. In particular, to identify the degree to which differences between teams are due to casemix. Methods Data were collected about the services provided to a random sample of patients from 15 CMHT caseloads, including contact with CMHT staff, other specialist mental health and social care services. The relationship between patients' needs and service receipt was explored. Results Information was obtained for 1396 patients. Average time on CMHT caseloads was 11.6 months, but there were marked between‐team differences. The proportion of re‐referrals also varied from under a tenth to over half. People with functional mental health problems and complex needs were most likely to be long‐term CMHT clients. The proportion of patients seen by a consultant in the previous 6 months ranged from approximately a fifth to almost all. Differences with respect to contact with other qualified practitioners were less marked. Older people with functional disorders, challenging behaviour and at least one medium risk had the most regular contact with CMHT staff. Risk of self‐harm, delusions and paranoia increased the likelihood of consultant involvement. Support workers were more likely to see people at risk of self‐neglect. The receipt of other services, including day hospitals and inpatient care varied greatly. Conclusions Considerable diversity was found in the length, nature and frequency of services provided to patients with different needs. Differences between teams were not wholly explained by case mix. Copyright © 2014 John Wiley & Sons, Ltd.